FINANCING GROWTH AND BANK RISK: EMPIRICAL EVIDENCE FROM INDONESIA - Wastuti, Wahyu; Prasetyowati, Riris Aishah; Anggraini, Ratna (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2024)
This study examines the crucial issue of the impact of financing growth on various dimensions of Islamic Banks in Indonesia. The growth of financing affects bank risk, profitability, and solvency. The main objective explains the relationship between financing growth and key performance indicators. The study uses ROA for profitability, EQTA for capital adequacy, NPF for bank risk, and the natural logarithm of Total Assets as a proxy for bank size. LIQD and CIR are included as additional variables to provide a more comprehensive analysis. Data for the period Q1 2012 to Q4 2020, obtained from the publication report on the OJK website. Using multiple linear regression, the findings showed a negative relationship between bank risk and financing growth. In addition, the growth of financing has a positive effect on both profitability and solvency of banks. This confirms the importance of prudential principles to optimize risk management strategies, especially in the context of a growing role in financing growth in Islamic banks.